Key issues in crime and punishment - Chambliss, William J. (SAGE, 2011)
Topics in this title include such hotly debated topics as accountability, arrest practices, bounty hunters, entrapment, Miranda warnings, police privatization, profiling, vigilantes and sero-tolerance policing.